Impact of credit on household food security: The case of Omo microfinance institution in southern Ethiopia - Boltana, Amanuel; Tafesse, Alula; Belay, Abrham; Recha, John W.M.; Osano, Philip M. (Elsevier, 2023)
To effectively address the pressing issue of insufficient food production and limited purchasing power among rural farm households in Ethiopia, it is of utmost importance to empower them through comprehensive developmental mechanisms and evaluate the effectiveness of these activities. By providing financial services to smallscale farmers and entrepreneurs, Omo microfinance plays a vital role in empowering individuals and communities to improve their livelihoods and contribute to the overall food security of the nation. The study assessed the impact of credit utilization on household food security among rural borrowers in the Offa district of Southern Ethiopia. Through the implementation of a multi-stage sampling technique, a total of 352 credit users and nonuser groups were selected for rigorous analysis. Data collection was conducted via a semi-structured interview schedule. The Propensity Score Matching (PSM) method was used for data analysis. The compelling results of this study reveal the significant and positive role of credit intervention in enhancing household food security. Credit utilization has led to a remarkable increase in the average calorie intake per capita per day, amounting to 248.53 kcal/day. The finding of this paper provides a case study for policymakers to give more attention to creating an enabling environment for microfinance institutions to develop appropriate products and services for rural farming households to address food insecurity in Ethiopia.